Travel and Tours Management System: Human Resource II (Leave Management, Time and Attendance, (Shift and Scheduling, Timesheet Management), Claims and Reimbursement, Payroll, Compensation Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Travel and Tours Management System is a comprehensive system that managestransactions related to travel and tours, creating itineraries, hiring staff, financial costs, andexecutive management. Human Resource II is in charge of dealing with problems or demandsof people that happen inside an organization. They often oversee the hiring, firing, andonboarding of new workers, as well as the orientation process to assist employees, etc. Whenconflicts emerge among employees, HR professionals must complete records of every actiontaken against an employee for legal reasons.The Mblitz Travel and Tours management system is an innovative Human Resource Systemthat uses facial recognition to track an employee's daily time in and out. This method ofverifying an individual's identification using their face to prevent wrongdoing will not bedeceived by the employee and will provide real-time visibility. Human Resources at MblizTravel & Tours requires extra protection to prevent information theft, so the Mblitz Travel andTours Management System was developed to protect the data stored by HR. Lastly, ournetwork design is an iterative process that includes topological design, network synthesis, andnetwork realization, aimed at ensuring that a new telecommunications network or servicemeets the needs of the subscriber and operator. They suggest we be more precise because itis essential to know what tools we use.As a result of the discussion within our system, the project improved the HR process byimplementing the advanced system of Human Resource II. Facial recognition has beenadded, automating the daily records of our employees. The travel and tours offer moreconvenience for securing individual identification with the use of real-time visibility, avoidinginformation theft, and iterative process meets the needs of our service. This is the strategy ofbeing accountable for finishing travel and tours human resource II.
Keywords: IT & Management